Integrasi Standar Akreditasi BAN-S/M dengan Nilai-Nilai Islam dalam Sistem Penjaminan Mutu di MA Minhajul Haq Purwakarta: Sebuah Model Holistik - Sulaeman, Rudi; Abdurahman , Isrun; fauzan, naufal; qiqi, qiqi; Suntiah , Ratu; Indah Sabila, Anisa (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Singaperbangsa Karawang, 2025)
This research is motivated by the dual challenges faced by Islamic educational institutions, particularly madrasas, in maintaining their Islamic identity while simultaneously meeting the demands of national quality standards. The research gap lies in the absence of studies that deeply analyze the organic and holistic integration between the eight National Education Standards (BAN-S/M) with Islamic values ​​in a coherent quality assurance model. The purpose of this research is to analyze the implementation and formulate such an integration model at MA Minhajul Haq Purwakarta. The method used is qualitative with a case study design. Data were obtained from document analysis (vision-mission, curriculum, internal quality standards) and enriched by in-depth interviews. The results of the study revealed that integration occurs organically and synergistically in every component of BAN-S/M, with Islamic values ​​as the foundation and spirit. The main finding is the formulation of the MINHAJ Holistic Quality Assurance Model consisting of three core layers: (1) Basic Layer (Islamic Values), (2) Process Layer (Integration of SNP and Pesantren System), and (3) Result Layer (Kaffah Graduates). In conclusion, this model not only addresses the dichotomy between Islamic identity and accreditation requirements, but also offers an innovative theoretical-practical framework for madrasas to produce graduates who are both academically competent and possess a strong Islamic character. The implications of this model can serve as a reference for developing accreditation policies that are more responsive to the specifics of Islamic education.